2004
DOI: 10.1159/000076494
|View full text |Cite
|
Sign up to set email alerts
|

Xanthoma disseminatum with Large Plaques Confined to the Back, Pulmonary Involvement and Multiple Intestinal Xanthomas

Abstract: Xanthoma disseminatum (XD) is a rare benign mucocutaneous xanthomatosis that is classified as a benign non-Langerhans cell histiocytosis. We report a 68-year-old man who presented with peculiar, large plaques confined to the back 7 years after the onset of cranial diabetes insipidus. Histopathological features of the cutaneous lesions were typical of XD. The patient had lower respiratory tract involvement with histiocytic infiltrates, which was unresponsive to various treatments and resulted in a fatal outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In most of the aforementioned cases, distinction is readily achieved on the basis of their differing clinical features; however, by virtue of its similar morphologic features and propensity for widespread involvement, the latter may potentially be confused with ECD. Xanthoma disseminatum is generally characterized as a benign disseminated mucocutaneous xanthomatosis [5]; nevertheless, there are reports of cases bearing overlapping features with ECD, including diabetes insipidus [1,15], and long bone involvement [18], and fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the aforementioned cases, distinction is readily achieved on the basis of their differing clinical features; however, by virtue of its similar morphologic features and propensity for widespread involvement, the latter may potentially be confused with ECD. Xanthoma disseminatum is generally characterized as a benign disseminated mucocutaneous xanthomatosis [5]; nevertheless, there are reports of cases bearing overlapping features with ECD, including diabetes insipidus [1,15], and long bone involvement [18], and fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, typical gastric xanthomas are well-demarcated whitish plaques or nodules. Similarly, cases with xanthomas in the sigmoid colon and rectum, showing multiple, well-defined, and whitish-yellow lesions, have been previously reported [4, 5]. Weinstock et al reported a case consistent with xanthoma presenting as flat, yellow, and irregularly shaped lesions in the sigmoid colon [6].…”
Section: Discussionmentioning
confidence: 85%
“…They are most commonly identified incidentally on colonoscopy and usually present as nodules, plaques, or patches [8]. It is rare to see these lesions presenting as masses suspicious for malignancy [9]. Diseases other than xanthomas that present with yellow to white lesions in the colon include pseudomembranous colitis, lipomas, and lymphomas.…”
Section: Discussionmentioning
confidence: 99%